Azide–acetonitrile "click" reaction triggered by Cs2CO3: the atom-economic, high-yielding synthesis of 5-amino-1, 2, 3-triazoles1. Issue 76 (19th August 2015) - Krishna, Patoju M.; Ramachary, Dhevalapally B.; Peesapati, Sruthi
<x xml:space="preserve">Abstract</x> Medicinally important 5-amino-1, 2, 3-triazoles were synthesized using a novel Cs2CO3-catalyzed azide–acetonitrile [3 + 2]-cycloaddition. Aryl azides and aryl acetonitriles were employed in this transformation resulting in excellent yields with high regioselectivity.